(untitled) (Research, Society and Development, 2021)
The Human Immunodeficiency Virus, popularly known as HIV, is the causative agent of AIDS (Acquired Immunodeficiency Syndrome), which affects the immune system, leaving the infected organism susceptible to contracting other opportunistic diseases caused by other viruses, bacteria, fungi or protozoa that cause complications and can lead to death. The first reports of AIDS in Brazil emerged in the early 1980s, with a very rapid spread in all regions of the country, however, the prevalence of cases in a greater proportion is still found today among heterosexuals in the South and Southeast from Brazil. A few decades have passed since the discovery of HIV, and even though the country is positioning itself in relation to the fight against the disease and with advances in treatment, it is clear that the epidemic is far from being controlled, and that the rates of new annual cases are still have been quite expressive. This research aims to analyze through statistical data over the years, which population is most affected by HIV/AIDS infection in Brazil, how the treatment is given and what is its relationship with opportunistic diseases.